The unashamed guide to virtual management : virtual workforce, virtual teams, virtual meetings, virtual office romances - Bisbee, Ben; Wisniewski, Kathy (ATD Press, 2019)
"Working remotely is a reality of today's and tomorrow's workforce. With organizations switching from a model of only on-site employees to on-site and virtual employees workintg globally, mangers need guidance on how to address the traditional and not-so-traditional issues that occur when staff is not colocated."--Back cover